Logical-Structural Model of Analysis of Financial Security of Priority Branches of National Economy - Kunytska-Iliash, M. V.; Kravchyk, Yu. V. (Statistics of Ukraine, 2022)
The article emphasizes the urgency of considering the development of methods of analyzing financial security at the level of sectoral economic system. The aim of the article is to develop a logical-structural model for analyzing the financial security of priority sectors of the national economy. The structural and functional components of financial security of the industry are identified, namely investment, credit, debt, tax, monetary, economic, insurance, production, innovation and technological, system and structural. Particular emphasis is placed on the relevance of improving the normative and methodological basis of state policy to ensure financial security just strategic (priority) sectors of the national economy, which, in turn, is a precondition for the social and economic development of the state. Based on the analysis of theoretical and methodological approaches to the formation of semantic and structural characteristics of economic security of the industry identified elements of methodological support for analyzing the financial security of strategic sectors of the national economy. The tasks of the methodology of financial security analysis of strategic sectors of the economy, such as financial and investment resources, proper financial condition, efficient use of capital, protection from financial risks and threats, development of financial subsystem, realization of potential in ensuring financial and economic development of the national economy. It is concluded that the elements of the logical-structural model of analysis of strategic sectors of the national economy are the purpose, objectives, components, indicators, approaches and methods for analysis and evaluation. The general purpose, indicators of analysis, and also an algorithm of methodology for analyzing as well as methodical approaches and methods of analysis and estimation of financial safety of priority branches of national economy are defined. The development of normative and methodological support for strategizing and implementation of state policy tools for strengthening the financial security of priority sectors of the national economy of Ukraine is outlined as a direction for further author’s research.